Hydroseeding application using pioneer local plant seeds for coal postmining soil in Tanah Laut Regency, South Kalimantan - M F Anshari; E. Boedianto; A A R Fernandes; E Arisoesilaningsih (Brawijaya University, 2018)
The research aimed to determine pioneer local plant seeds germination and growth on coal postmining soil, and to determine optimal mulch for producing great productivity. The research was conducted in two applications in a coal post mining area, Tanah Laut, South Kalimantan. The used seeds were 5 species of legumes, 3 species of grasses, and 3 species of sedges. Hydroseeding was applied by mixing seeds in mulch and spreading it on soil surface of 400 cm2 plots (1st application) and 10,000 cm2 plots (2nd application). There were five treatments in the 1st application and repeated four times, while in the 2nd, there were six treatments with three times repetitions. Germination rate, seedling density, plant coverage, height/length, and leaf length were observed every three days (1st application). On 60 days after sowing, root length and plant biomass (the 1st), and plant coverage, height and productivity (the 2nd) were measured. The results showed that hydroseeding mulches could be media for pioneer local plant seeds germination and seedling growth especially for Leguminosae. While the buffalo dung could be hydroseeding mulch for Poaceae growth. Although root/shoot ratio of Cyperaceae was higher than other families, Leguminosae root developed longer as shoot growth and well adapted on postmining soil. The hydroseeding mulch composed by 720 seeds per plot and applied 4 cm in depth was optimal based on seed germination percentage. Whereas mulch with 0.2 cm depth in 2nd application showed a higher effectivity for plant growth and productivity.